(untitled) (Scientific journal of the Fergana State University, 2024)
In modern cars, internal combustion engines are mainly common. Internal combustion engines by design are divided into piston and rotary. Reciprocating internal combustion engines are mainly used in cars.As a result of the combustion of fuel, the pressure created due to the expansion of the gas pushes the piston in a linear direction back and forth, thus driving the crankshaft in motion. The internal engine requires air and a combustible mixture to operate.